RECYCLING STUDIES AT UNIVERSITY CAMPUSES - Apaydin, O.; Erdem, O. (GLOBAL NEST, SECRETARIAT, 2013)
In the study, recyclable solid waste (RSVV) planning and characterization investigations were be performed institutional RSW at source in three campus areas of Yildiz Technical University in Istanbul. The paper outlines findings from a monthly study results on institutional RSW management at three campuses: Yildiz Campus, Davutpa a Campus and Ayaza.ga Campus. Yildiz Campus is located at Be ikta and has a population of 14538. Davutpa a Campus is located at Esenler and has a population of 12577. Ayaza.ga Campus is located at Si li and has a population of 3379. A new study and collection process is performed both Davutpa a Campus and Ayaza.ga Campus. There are four different collection boxes for collecting recyclable wastes at these two campuses: Metal, plastic, paper and glass. The colors of the boxes are different each other: The colors of metal, glass, paper and plastic boxes are yellow, white, green, and blue, respectively. Recycling studies at source in Yildiz Campus is continued with only one kind collection box: mixed box with blue color for paper, plastic, metal and glass wastes. The results and separation rate have been presented at the paper for studies done during 2011. Studies were conducted in order to separate RSW at source point and performed at all campuses of Yildiz Technical University. According to the results obtained from the study, total RSW amounts collected at source point in the campuses are 11 m3 and 3 ton per a day. In three campuses, amounts of collected RSW at source are obtained between 0.02 and 0.08 kg per person per a day.
Keywords: Istanbul; Recyclable solid waste; separation at source; university campus; Yildiz Technical University; Engineering; Environmental Sciences & Ecology